2018
DOI: 10.1021/acs.langmuir.8b00286
|View full text |Cite
|
Sign up to set email alerts
|

Polyols-Infused Slippery Surfaces Based on Magnetic Fe3O4-Functionalized Polymer Hybrids for Enhanced Multifunctional Anti-Icing and Deicing Properties

Abstract: High durability, low cost, and superior anti-icing and active deicing multifunctional surface coatings, especially in the extreme environment, are highly desired to inhibit and/or eliminate the detriment of icing in many fields, such as automobile, aerospace, and power transmission. Herein, we first report a facile and versatile strategy to prepare novel slippery polyols-infused porous surfaces (SPIPS's) with the inexpensive polyols as the lubricant liquids. These SPIPS's are fabricated by a spray-coating appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 39 publications
0
60
0
Order By: Relevance
“…While direct mechanical and centrifuge testing represent the majority of the research found in the current literature [11][12][13][14][15][20][21][22][23][24], additional miscellaneous tests have emerged that involve various apparatuses and methodologies, and these will be discussed separately in this review. Mechanical testing can be further classified according to the four common direct methods, including horizontal shear test [10,[25][26][27][28][29][30][31][32][33][34][35], vertical shear test [11,36], and tensile test [37][38][39], which are schematically depicted in Figure 1. Unlike centrifuge testing, mechanical testing can be conducted on stationary equipment, such as a tensile testing machine or a cold plate with a push rod [27,28,36].…”
Section: Ice Adhesion Testing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While direct mechanical and centrifuge testing represent the majority of the research found in the current literature [11][12][13][14][15][20][21][22][23][24], additional miscellaneous tests have emerged that involve various apparatuses and methodologies, and these will be discussed separately in this review. Mechanical testing can be further classified according to the four common direct methods, including horizontal shear test [10,[25][26][27][28][29][30][31][32][33][34][35], vertical shear test [11,36], and tensile test [37][38][39], which are schematically depicted in Figure 1. Unlike centrifuge testing, mechanical testing can be conducted on stationary equipment, such as a tensile testing machine or a cold plate with a push rod [27,28,36].…”
Section: Ice Adhesion Testing Methodsmentioning
confidence: 99%
“…Unlike centrifuge testing, mechanical testing can be conducted on stationary equipment, such as a tensile testing machine or a cold plate with a push rod [27,28,36]. As a result, the ice that dislodges using a mechanical testing approach is typically preserved and can be quickly assessed for surface irregularities [30,31,35]. By contrast, centrifuge testing typically results in the destruction of the ice sample, as it impacts the wall of the centrifuge testing chamber and is consequently destroyed [22][23][24].…”
Section: Ice Adhesion Testing Methodsmentioning
confidence: 99%
“…[ 144 ] On the other hand, Zhang et al infiltrated polyols, instead of water‐immiscible lubricants, within the Fe 3 O 4 ‐embedded polymer substrates to fabricate photothermal SLIPS coating. [ 145 ] These hydrophilic lubricants exhibited a much lower ice adhesion strength compared with silicone oils.…”
Section: Sustainable Applications Of Photothermal Materialsmentioning
confidence: 99%
“…friendly and energy efficient. Notably, a number of photothermal conversion materials including carbon materials, conjugated polymers, two-dimensional nanostructural materials, and metallic particles have also been applied as SASs (28,(31)(32)(33)(34). Although remarkable improvements have been made, some challenges have yet to be tackled.…”
mentioning
confidence: 99%